1990
DOI: 10.1159/000243188
|View full text |Cite
|
Sign up to set email alerts
|

<i>Cis</i>- and <i>Trans</i>-Isomeric Fatty Acids in Plasma Lipids of Newborn Infants and Their Mothers

Abstract: The proportionate fatty acid composition of plasma lipids was determined by high-resolution gas-liquid chromatography in 30 pairs of mothers and their term infants at the time of birth. Trans-fatty acids were found at similar percentage levels in maternal and infantile plasma, evidence for the first time of their placental permeability. In umbilical plasma, linoleic and alpha-linolenic acids contributed markedly smaller portions to total fatty acids, in contrast to clearly higher proportions of their long-chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
3
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 31 publications
6
39
3
5
Order By: Relevance
“…2). However, we do not observe as Koletzko [17,21] correlation between 18:1 t and TFAs (Table 2). TFAs represent on average 0.20% of the total fatty acids and the predominant isomer is the 18:1 (0.14%) isomers.…”
Section: Total Phospholipids In the Walls Of The Cord (N = 30)contrasting
confidence: 64%
See 2 more Smart Citations
“…2). However, we do not observe as Koletzko [17,21] correlation between 18:1 t and TFAs (Table 2). TFAs represent on average 0.20% of the total fatty acids and the predominant isomer is the 18:1 (0.14%) isomers.…”
Section: Total Phospholipids In the Walls Of The Cord (N = 30)contrasting
confidence: 64%
“…As in the PLT of the arterial walls, negative correlations were found between 18:2 ct and arachidonic acid (AA) (r = 0.98, p < 0.001) and 20:4 n-6/18:2 n-6. There is therefore competition between the 18:2 ct and the EFAs and not a competition with the 18:1 trans as Koletzko [17] had found. Although the rate of 18: t is low, we think it is important to emphasize this correlation which could reflect the isomers of linoleic acid isomers to interfere with the conversion of the latter to 20:4 n-6, with potential repercussions on prostaglandin synthesis as discussed since PC is a reserve of 20:4 n-6, precursor of prostaglandins.…”
Section: Venous Walls Of the Cord (N = 7)mentioning
confidence: 88%
See 1 more Smart Citation
“…Other studies have also reported strong correlations between maternal and infant plasma trans fatty acid concentrations (Koletzko and Muller, 1990;Craig-Schmidt, 2001). To the best of our knowledge, no study has directly examined the influence or association between maternal trans fatty acid intake and early postpartum infant adiposity.…”
Section: Discussionmentioning
confidence: 90%
“…Ces valeurs sont 3 fois plus faibles que celles rapportées par Koletzko [9] pour la population allemande. On observe chez le foetus les mêmes isomères que chez la mère, mais leurs proportions respectives sont différentes.…”
Section: Passage Des Isomères Trans De La Mère Au Foetusunclassified